PENGARUH AKUN TIKTOK ANDREAS LUKITA TERHADAP IMPULSE BUYING REMAJA WANITA - Alya Fathimah (2021)
Andreas Lukita is one of the influencers who likes to share product reviews on the TikTok application. One of the unique characteristics of Indonesian consumers is impulse buying. Impulsive behavior is often associated with teenagers because of the character of teenagers who like to follow the latest trends. This study was conducted to determine whether or not there is and how much influence Andreas Lukita's TikTok account has on impulse buying for teenage girls. This study uses cognitive response theory to analyze the message processing process on impulse buying behavior. The approach in this research is quantitative. The method used is a survey distributed to 100 female TikTok followers Andreas Lukita. The research shows that the t-count value is 13,585 which is greater than the t table, which is 1.9842, which means Ha is accepted that there is an influence between Andreas Lukita's TikTok account on impulse buying for young women with a correlation value of 0.808 which shows a very strong relationship and the coefficient of determination is equal to 65.3% which shows that Andreas Lukita's TikTok account followers feel an influence on Andreas Lukita's TikTok account on impulse buying